Low level of antimicrobial resistance in Escherichia coli among Swedish nursing home residents. (February 2013) - Olofsson, Magnus; Toepfer, Michael; Östgren, Carl Johan; Midlöv, Patrik; Matussek, Andreas; Lindgren, Per-Eric; Mölstad, Sigvard
Abstract Background: Screening for bacterial colonization and antimicrobial resistance (AMR) among a defined population could aid in the identification of at-risk populations and provide targets for antibiotic stewardship and infection control programmes. Methods: Two hundred and sixty-eight participants at 11 Swedish nursing homes underwent serial screening for colonization with Escherichia coli between March 2008 and September 2010. Seventy-two of the 268 participants (27%) were male. The median age was 85 y. Samples were collected from urine, the rectal mucosa, the groin, and active skin lesions. Results: Two hundred and nine of 268 participants (78%) were colonized with E. coli at any body site/fluid. The specific colonization rates were 81% (rectum), 48% (urine), 30% (groin), 59% (unknown), and 13% (skin lesion). An antibiotic-resistant E. coli isolate was identified in 18% of all participants regardless of colonization status; all together, 87 resistant isolates were detected. Only 1 participant carried isolates with resistance to third-generation cephalosporins (cefotaxime and ceftazidime). Conclusions: The presence of resistance was generally low, and the greater part of the resistant cases was connected with 3 common antibiotics: ampicillin, trimethoprim/sulfamethoxazole, and ciprofloxacin. In spite of generally increasing resistance against third-generation cephalosporins in E. coli in Sweden, this study does not implicate residence at a Swedish nursing home as a risk factor for the acquisition of expressed cephalosporin resistance.